Symptomatic malignant ascites drainage with a patient-controlled vascular catheter: interim analysis of safety and patient-reported outcomes - Stukan, Maciej; Jędryka, Marcin; Cokan, Andrej; Klát, Jaroslav; Ndukwe, Munachiso Iheme; Kryszpin, Marcin; Poblocka, Renata; Timošek, Eva; Romanová, Martina; Balcarová, Klára; Madry, Radoslaw; Cibula, David (Supportive care in cancer, 2025)
Malignant ascites (MA) and repeated paracentesis can impair a patient's quality of life (QOL). The aim was to perform an interim analysis of safety and changes in patients' QOL in an ongoing prospective, multicentre (conducted within the Central and Eastern European Gynaecologic Oncology Group (CEEGOG)) trial on symptomatic MA drainage with a patient-controlled central vascular catheter (CVC) inserted into the abdominal cavity. CVC (14-Ga) was inserted into the abdominal cavity of patients with symptomatic MA, and drainage was controlled by patients at home. The rate and quality of complications were classified according to Common Terminology Criteria for Adverse Events Version 5.0. QOL was evaluated before and 10-14 days after/during drainage with standardized QLQ-C15-PAL, SGA, and FACIT-TS-G questionnaires. Wilcoxon and Chi-squared tests were used. Among 113 recruited patients (2015-2022), seven patients experienced complications (6.2%), and there was one patient with a serious adverse event (death on the 9th day after catheter insertion, classified as not related to the intervention). Adverse events included local infection (n = 2) (resolved after oral antibiotics), catheter obstruction (n = 2), catheter self-removal (n = 2) (re-insertion performed), and nausea (n = 1). When comparing the assessment before and after/during drainage, we found the significantly better global QOL (mean 31.8 vs. 47.8, p < 0.001), improvement in physical (52.6 vs. 64.4, p < 0.001) and emotional functioning (50.7 vs. 65.4, p < 0.001); symptoms were significantly less intense: fatigue (66.7 vs. 50.9, p < 0.001), nausea and vomiting (37.8 vs. 21.4, p < 0.001), pain (53.9 vs. 34.1, p < 0.001), dyspnoea (48.5 vs. 22.3, p < 0.001), insomnia (49.1 vs. 34.3, p < 0.001), appetite loss (56.3 vs. 40.3, p < 0.001), and constipation (31.0 vs. 25.2, p = 0.007), and more patients had no pain on eating (71.3% vs. 82.9%, p = 0.04). Most patients (78%) were satisfied, 83% would recommend the procedure to others, and 90% would choose intervention again. The interim analysis provided data on the safety and improvement of patients' QOL after MA drainage via patient-controlled CVC inserted into the abdominal cavity, thus justifying the continuation of recruitment for the main trial without changes in the protocol.
Keywords: senioři; ascites; senioři nad 80 let; Middle Aged; průzkumy a dotazníky; mužské pohlaví; Prospective Studies; Patient Reported Outcome Measures; Adult; kvalita života; Ascites; Neoplasms; Aged, 80 and over; ženské pohlaví; Humans; prospektivní studie; hodnocení výsledků péče pacientem; nádory; Surveys and Questionnaires; lidé středního věku; drenáž; dospělí; Female; Quality of Life; Aged; lidé; Male; Drainage